Performance of Methylococcus capsulatus based microbial and enzymatic proton exchange membrane fuel cells. (August 2022) - Samarasinghe, Nalin; Longtin, Nicole; Fernando, Sandun
Abstract: Activation of methane in low-temperature fuel cells has been a challenge due to its thermodynamic stability. In this study, we demonstrate the feasibility of using a pure culture of Methylococcus capsulatus microbial fuel cell in a proton exchange membrane (PEM) fuel cell in whole-cell and crude enzymatic modes. The impact of time and mediators of the microbial fuel cells (MFCs) was studied. Additionally, a mathematical model was used to predict and explain the fuel cell's electrochemical performance and mechanic details. The fuel cell generated an open-circuit voltage of 378.91 mV and a power density of 438.57 μW/m 2 in the whole-cell mode, whereas an OCV of 125.62 mV and a power density of 117.94 μW/m 2 in the enzymatic mode without the use of an external mediator. Although the cell was stable throughout the test duration of ten days in the whole-cell mode, the stability declined within minutes in the enzymatic mode. This work demonstrates the feasibility of generating electricity via a proton exchange membrane (PEM) fuel cell in microbial and enzymatic modes using methane as the only carbon source at room temperature with a pure culture of M. capsulatus as a direct electron-transporting biocatalyst.